Effect of Diabetes Mellitus on Hypogonadism in Chronic Renal Failure - Savas Karatas; Sennur Kose (Medical Laboratory Technology Journal, 2022)
Hypogonadism in male patients with chronic renal failure and diabetes mellitus has been known separately; up to now, the effect of these two diseases together on testosterone deficiency and the impact of testosterone deficiency on metabolic values have not been known precisely, therefore in this study we aimed to investigate testosterone deficiency in patients with diabetes mellitus and chronic renal failure. Eighty-seven chronic renal failure patients and 45 control patients who were followed at endocrinology and nephrology clinics were included in the study. After exclusion criteria, the patients were divided into two groups according to diabetes mellitus status. Groups were compared according to testosterone levels. Testosterone deficiency and good groups were compared to blood glucose, Hba1c, and lipid profile levels. The mean age of 87 CRF patients and 45 people in the control group were similar (59.85 ± 9.99 and 56.67 ± 8.56, respectively, p= 0.16). Testosterone deficiency was 24.1% (21/87) in CRF group and 8.8% (4/45) in control group (p= 0.04). The total testosterone levels were notably lower in the diabetic-CRF patients, 3.44 ± 1.3 vs. 4.26 ± 1.46 mg/dl (p= 0.02). The testosterone deficient CRF group had higher blood glucose and HbA1c according to the testosterone sufficient group. (161.20 ± 61.24 mg/dl vs 133.25 ± 59.87 mg/dl blood glucose, p= 0.04 and 7.54 ± 1.46 vs 6.79 ± 1.14 % HbA1c, p= 0.04). Serum triglyceride and LDL levels did not significantly change between groups (p= 0.20 and 0.76, respectively). Testosterone deficiency in male CRF patients is not uncommon. Male patients with both T2DM and CRF have more common testosterone deficiency. In testosterone-sufficient patients, blood glucose regulation was better. Therefore, in these patients, it may be helpful not to neglect testosterone deficiency, which affects gonadal function, body metabolism, and cardiac and skeletal health.